Impact of Prostate Cancer and Its Treatment on the Outcomes of Ileal Pouch-Anal Anastomosis. Issue 12 (December 2017) - Lian, Lei; Ashburn, Jean; Remer, Erick M.; Remzi, Feza H.; Monga, Manoj; Shen, Bo
Abstract : Background: There are scant published data in the impact of prostate cancer and its treatment on functional outcomes and quality of life (QOL) in patients with ileal pouch-anal anastomosis (IPAA). The aim of the study was to evaluate the influence of prostate cancer and its treatment on functional outcomes and QOL in patients with IPAA. Methods: Patients with IPAA with prostate cancer were compared to age and pouch duration–matched controls without prostate cancer in a 1:2 ratio. Pouch function and QOL were compared between pretreatment and posttreatment for prostate cancer as well as between subjects and controls. Results: A total of 30 patients with IPAA with prostate cancer and 60 matched controls were included. Treatment modalities of prostate cancer included prostatectomy (n = 22), brachytherapy (n = 5), watchful waiting (n = 2), and hormonal therapy (n = 1). The median length of follow-up was 6 (interquartile range, 2.7–8) years. Permanent fecal diversion was required in 5 (16.7%) patients with prostate cancer who developed pouch failure, as compared with 2 patients in the control group ( P = 0.04). In patients who retained their pouches, the pouch functional outcomes at the latest follow-up were similar to that before prostate cancer treatment and to that of the matched controls, in terms of bowel movements, daytime seepage, nighttime bowel movements, nighttime seepage, and QOL score. Conclusions: The risk of pouch failure may be increased after the diagnosis of prostate cancer with or without treatment. However, for those with retained pouches, their pouch function and QOL did not seem to be adversely affected. Abstract : Article first published online 6 October 2017.